Analisis Energi Surya - Angin Hibrida untuk Mendukung Sistem Pengeringan Ikan Berbasis Energi Terbarukan - Nasution, Fakhruddin Ahmad; Multazam, Teuku; Sahputra , Ilham (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study analyzes the potential and optimization of a solar–wind hybrid power generation system to support sustainable anchovy drying for small-scale fishermen in Ujong Blang Village, Lhokseumawe, Aceh. Field data on wind speed and air temperature were collected on September 20–21, 2025. The measurements indicate that solar energy has a more dominant contribution with an estimated production of 3.7 kWh/kWp·day, while wind energy provides only around 0.37 kWh/m²·day at an average speed of 2.93–5.29 m/s. To meet the energy demand of a 50 kg/hour fish dryer (3.8 kW), a PV capacity of 4.1 kWp is required for 4 hours of operation or 8.3 kWp for 8 hours. Meanwhile, wind energy requires relatively large turbine swept areas, making it more suitable as a complementary source. The optimal hybrid configuration positions solar PV as the primary source (70–80%), wind turbines as a secondary source (20–30%), and batteries for energy storage. The results demonstrate that a solar–wind hybrid system can enhance the reliability of renewable energy supply efficiently and sustainably to support fish drying operations.